Avaliação das moléculas HLA-G e PD-L1 em pacientes submetidos a transplante renal em Goiânia - GO - Botelho, Silvia Marçal (2020)
Kidney transplantation (KT) is the treatment of choice for patients with end-stage renal disease. In KT, the HLA-G and PD-L1 molecules due to their tolerogenic action are of clinical and therapeutic interest. The aim of this study was to evaluate the HLA-G and PD-L1 molecules at different moments in the KT. 124 patients were evaluated. Of these, 114 were previously transplanted (Group of old patients-GOP) and, in 10 patients, the evaluation started in the pre-KT (Group of new patients-GNP). In the GOP a cross-sectional study with a single blood collection, while in the GPN a 12-month follow-up was carried out with serial blood collection. Patients who had graft dysfunction were submitted to renal biopsy samples and immunohistochemistry was performed for both molecules (GNP). The study execution phase took place from March/2016 to December/2017. In GOP the use of corticosteroids+calcineurin inhibitor +azathioprine as an initial immunosuppression regimen (p<0,001), the presence of one or two episodes of rejection (p <0,001), and CMV infection (p= ,006) were correlated with a low dosage of HLA-G. Having performed 6-10 hemodialysis sessions in post-KT was associated with a high dose of HLA-G (p=0,02). In GNP the occurrence of rejection episodes was associated with low expression of HLA-G (p<0,001) and PD-L1 (p<0,001). The variable time after KT (p<0,001) was associated with a lower level of HLA-G. Transfused patients had low levels of PD-L1 (p=0,03). Increased levels of HLA-G (p=0,001) and PD-L1 (p<0,001) were observed in female patients. Patients who received a kidney from a related live donor expressed more HLA-G (p<0,001). The study concluded that the aforementioned variables, which were positively and negatively associated with the levels of HLA-G and PD-L1 can promote the stability or instability of the grafts respectively, maintaining renal function or perhaps providing rejection processes.